Producing Good Citizens Literacy Training in Anxious Times - Wan, Amy J. (Pitt Comp Literacy Culture, 2014)
deliberations on citizenship and literacy, and other materials from the period to reveal the goal and rationale behind each program. Wan relates the enduring bond of literacy and citizenship to current times, by demonstrating the use of literacy to mitigate economic inequality, and its lasting value to a productivity-based society. Today, as in the past, educators continue to serve as an integral part of the literacy training and citizen-making process